Epistimologi Pendidikan Islam: Studi Landasan Konseptual Pembelajaran Menurut Al-Qur’an - Imron Rosyadi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2018)
The conceptual foundation of learning is a philosophical assumption that is used as a starting point in the context of study and learning practice. The assumptions that become the starting point in the context of learning come from various sources, namely religion, philosophy, and law. Based on these sources, the types of learning foundations can be identified as the religious basis of learning, the philosophical basis of learning, and the juridical basis of learning. Learning will be carried out properly, with clear directions for its objectives, relevant curriculum content, and effective and efficient methods or methods of implementation only if carried out with reference to a solid foundation. Therefore, before carrying out education, educators need to first strengthen their educational foundation. Given the nature of education is humanization, namely efforts to humanize humans, educators need to understand human nature as one of the foundations. The concept of human nature adopted by educators will have implications for the concept and practice of education. Islam is a religion that carries a mission so that its people carry out education and teaching. Based on this religious foundation that learning and teaching is worship because it is a commandment, is a manifestation of servitude to Allah SWT which has the same value as jihad fi sabilillah, education lasts a lifetime which is a never-ending process.